EVOLUCIÓN DE LA PRODUCCIÓN AUDIOVISUAL EN CINCO CIBERMEDIOS ESPAÑOLES - Javier Mayoral Sánchez (Fonseca, Journal of Communication, 2023)
This paper quantifies and analyzes the evolution of audiovisual production of five Spanish digital newspapers: abc.es, elconfidencial.com, elmundo.es, elpais.com and lavanguardia.com. So have been studied videos published on the five cover for four weeks (fourteen days in November 2011 and another fourteen in March 2014). This diachronic perspective has revealed a remarkable contradiction in online media about audiovisual products. Even with very considerable differences between them, the five analyzed media increasingly publish videos.